On the curious association of diaphragmatic hernia and Urban-Rifkin-Davis Syndrome (Autosomal Recessive Cutis Laxa-1C): A collective review of 16 cases - V Raveenthiran; Nagarajan Darun; Dhayalan Pavithra; Prakash Gambhir (EL-Med-Pub, 2024)
Background: Autosomal recessive cutis laxa type-1C is also known as Urban-Rifkin-Davis syndrome (URDS). It is known to affect cardiopulmonary, integumentary, gastrointestinal, musculoskeletal and genitourinary systems. However, its frequent association with congenital diaphragmatic hernia has not previously been highlighted. Case Presentation: A newborn male with cutis laxa presented with respiratory distress at birth. The cause of dyspnoea was perinatal strangulation of the stomach in hiatus hernia. After surgical repair of the hernia, his respiratory distress temporarily improved but kept recurring periodically by various mechanisms in sequence namely pulmonary hypertension, tracheomalacia, pulmonary emphysema and finally he succumbed to pneumothorax. Genetic analysis revealed his skin condition as autosomal recessive cutis laxa type-1C which is also known as URDS. Exome sequencing revealed a novel frameshift mutation c.426delC (p.Cys143Alafs*41) of the LTBP4 gene in the exon 5 of Chromosome 19.  Conclusion: Out of the 28 cases of URDS reported in the world literature 57% had congenital diaphragmatic hernia (CDH) and 53% of them died during infancy. Such a high incidence of CDH is not observed in other subtypes of elastic disorders. Thus, congenital diaphragmatic defects appear to be a characteristic diagnostic feature of URDS in patients with cutis laxa.